E-GOVERNANCE IN THE PUBLIC SECTOR IN ALGERIA: CHALLENGES AND PROGRESS - Bouguetaia , Soufyane; mezouri , Ettayib (The journal of contemporary issues in business and government, 2024)
This paper investigates the e-government landscape in Algeria, analyzing its progress, challenges, and readiness. Algeria's digital transformation journey is marked by advancements in infrastructure, digital literacy, and online services, alongside persistent issues like the digital divide and the need for data security enhancement. The study also delves into Algeria's global ranking in the e-government domain, shedding light on its international standing. Furthermore, the paper explores the profound impact of e-government on enhancing the quality and accessibility of public services, making them more responsive to citizens' needs and expectations. The conclusion highlights Algeria's promising path toward comprehensive egovernment. With continued efforts in infrastructure development, addressing digital disparities, and reinforcing data security, Algeria is well-positioned to create a more efficient and citizencentric governance model. This paper provides valuable insights into the challenges and opportunities that define Algeria's evolving e-government landscape.